Evaluasi Program Bimbingan dan Konseling Dalam Mengatasi Perilaku Membolos Peserta Didik di Sekolah Menengah Atas (SMA) Yp Unila Bandar Lampung - Defriyanto, Defriyanto; Rahayu, Dewi Jami (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2015)
School counseling and counseling services are a support service for either individual or group learners in order to solve the current problem. In the implementation of the service activities on the program that has succeeded by the supervising teacher by paying attention to the needs and problems of the learners. At the end of the service, one of the stages that must be performed by the supervising teacher is the evaluation. The problem in this research is how the implementation of guidance and counseling service program in overcoming the behavior of ditching students in High School YP Unila Bandar Lampung. This type of qualitative research is field research (field research) with the type of descriptive research. The population in this study are all students of class X, principal, student waka, and tutor. Data completion technique using interview method, observation and documentation. The results of this study indicate the implementation of evaluation activities guidance and counseling program in addressing the behavior of ditching class X students at YP Unila Bandar Lampung High School.